Responsivitas Pelayanan Pengaduan Masyarakat Di Kantor Kepolisian Sektor Alla Kabupaten Enrekang - Sofianti, Maya; Malik, Ihyani; Parawu, Hafiz Elfiansyah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
The purpose of this study was to analyze the level of responsiveness of public complaint services at the Alla Sector Police Office, Enrekang Regency. This  study used quantitative  with quantitative descriptive research type, while the number of informants in this study were 63 people. The data collection technique used a questionnaire in the form of a checklist and used descriptive analysis techniques. The results showed that the level of responsiveness of public complaint services at the Alla Sector Police Office in Enrekang Regency, which was measured using indicators  by Zeithaml, which consisted of indicators of responsiveness, accuracy of serving, and punctuality of service, which were in the quite good category, while the speed of serving indicators. , the accuracy of serving and the indicators of the ability to respond to community complaints were in the good category. Keywords: public service, public complaints, responsiveness